Protein-L-Isoaspartyl Methyltransferase (PIMT) Is Required for Survival of Salmonella Typhimurium at 42°C and Contributes to the Virulence in Poultry - Pesingi, Pavan K.; Kumawat, Manoj; Behera, Pranatee; Dixit, Sunil K.; Agarwal, Rajesh K.; Goswami, Tapas K.; Mahawar, Manish (Frontiers in Microbiology, 2017)
Poultry birds are asymptomatic reservoir of Salmonella Typhimurium (S. Typhimurium) but act as source of human infection for this bacterium. Inside the poultry, S. Typhimurium experiences several stresses, 42 ºC body temperature of birds is one of them. Proteins are highly susceptible to temperature mediated damage. Conversion of protein bound aspartate (Asp) residues to iso-aspartate (iso-Asp) is one of such modifications that occur at elevated temperature. Iso-Asp formation has been linked to protein inactivation and compromised cellular survival. Protein - L - isoaspartyl methyltransferase (PIMT) can repair iso-Asp back to Asp, thus enhances the cellular survival at elevated temperature. Here, we show that the pimt gene deletion strain of S. Typhimurium (∆pimt mutant strain) is hypersensitive to 42 ºC in vitro. The hypersusceptibility of ∆pimt strain is partially reversed by plasmid based complementation (trans-complementation) of ∆pimt strain. Following oral inoculation, ∆pimt strain showed defective colonization in poultry caecum, and compromised dissemination to spleen and liver. Interestingly, we have observed three and half folds induction of the PIMT protein following exposure of S. Typhimurium to 42 ºC. Our data suggest a novel role of pimt gene in the survival of S. Typhimurium at elevated temperature and virulence. Key words: isoaspartate, PIMT, Salmonella, 42 °C, poultry